The scientific impact of Einstein's visit to Argentina, in 1925 - Gangui, Alejandro (2014)
The arrival of Albert Einstein in Argentina in 1925 had an impact, equally relevant, on the scientific community and on the general public. In this paper we discuss that visit from three different perspectives. Firstly, we consider the conditions that allowed for such visit to be possible. Then we focus on the institutional actors that facilitated it, as well as on the expertise and written references on topics related to relativity theory circulating at the time in the local community. In the last section we consider the implications of that visit for the local scientific environment.